Evaluation and Management of Patients with Methomyl Poisoning – A Case Report - Pennisi, Leonardo; Lepore, Anna; Santacroce, Luigi; Gagliano-Candela, Roberto; Charitos, Ioannis Alexandros (Open Access Macedonian Journal of Medical Sciences, 2020)
The Apulian Poison Centre (PC) of Foggia, Italy, annually manages numerous consultations concerning certain or suspected poisonings from pesticides, starting at the same time a careful activity related to the risk assessment phase. The management of the exposure to pesticides and to other chemicals, and the alerting of the “National center for chemicals, cosmetics and consumer protection” at the Istituto Superiore di Sanità (ISS), actively contributes to the improvement of products quality and safety. Thus, leading to a reduction in the number of intoxications - and therefore of the accesses to the emergency services - allows greater protection for workers, bystanders, residents and consumers. The reported case of methomyl poisoning has been of fundamental importance both from the medical point of view and for the management of the intoxicated patient, both for the risk assessment actions, and for cooperation with the competent authorities, generating discussion points on the regulations in force between PCs and National Competent Authority. It follows that the feedback of intoxication in an emergency can lead to improvements in the management and risk mitigation measures in order to reach a greater protection of human, animal, and environmental health. In addition, the regulatory feedback deriving from these reports is an input to the increase product quality improvement (mixtures, labels, packaging, and risk communication) leading to a greater protection of potential exposed subjects. The importance of creating an information and management network that allows the optimization of the flow of information deriving from PCs arises. The actions taken are therefore described, both relating to the management of the emergency, and relating to the subsequent information flow and to the measures for containing the consequent risks.